Identification of Protein Quality Markers in Toad Venom from Bufo gargarizans - Meiyun Yang; Weiwei Huan; Guobing Zhang; Jie Li; Fengyan Xia; Rabia Durrani; Wei Zhao; Jidong Lu; Xinmeng Peng; Fei Gao (Molecules, 2023)
Toad venom is a traditional Chinese medicine with high medicinal value. The existing quality evaluation standards of toad venom have obvious limitations because of the lack of research on proteins. Thus, it is necessary to screen suitable quality markers and establish appropriate quality evaluation methods for toad venom proteins to guarantee their safety and efficacy in clinical applications. SDS-PAGE, HPLC, and cytotoxicity assays were used to analyze differences in protein components of toad venom from different areas. Functional proteins were screened as potential quality markers by proteomic and bioinformatic analyses. The protein components and small molecular components of toad venom were not correlated in content. Additionally, the protein component had strong cytotoxicity. Proteomics analysis showed that 13 antimicrobial proteins, four anti-inflammatory and analgesic proteins, and 20 antitumor proteins were differentially expressed extracellular proteins. A candidate list of functional proteins was coded as potential quality markers. Moreover, Lysozyme C-1, which has antimicrobial activity, and Neuropeptide B (NPB), which has anti-inflammatory and analgesic activity, were identified as potential quality markers for toad venom proteins. Quality markers can be used as the basis of quality studies of toad venom proteins and help to construct and improve safe, scientific, and comprehensive quality evaluation methods.